If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -2)(x + 8) = 2 Reorder the terms: (-2 + x)(x + 8) = 2 Reorder the terms: (-2 + x)(8 + x) = 2 Multiply (-2 + x) * (8 + x) (-2(8 + x) + x(8 + x)) = 2 ((8 * -2 + x * -2) + x(8 + x)) = 2 ((-16 + -2x) + x(8 + x)) = 2 (-16 + -2x + (8 * x + x * x)) = 2 (-16 + -2x + (8x + x2)) = 2 Combine like terms: -2x + 8x = 6x (-16 + 6x + x2) = 2 Solving -16 + 6x + x2 = 2 Solving for variable 'x'. Reorder the terms: -16 + -2 + 6x + x2 = 2 + -2 Combine like terms: -16 + -2 = -18 -18 + 6x + x2 = 2 + -2 Combine like terms: 2 + -2 = 0 -18 + 6x + x2 = 0 Begin completing the square. Move the constant term to the right: Add '18' to each side of the equation. -18 + 6x + 18 + x2 = 0 + 18 Reorder the terms: -18 + 18 + 6x + x2 = 0 + 18 Combine like terms: -18 + 18 = 0 0 + 6x + x2 = 0 + 18 6x + x2 = 0 + 18 Combine like terms: 0 + 18 = 18 6x + x2 = 18 The x term is 6x. Take half its coefficient (3). Square it (9) and add it to both sides. Add '9' to each side of the equation. 6x + 9 + x2 = 18 + 9 Reorder the terms: 9 + 6x + x2 = 18 + 9 Combine like terms: 18 + 9 = 27 9 + 6x + x2 = 27 Factor a perfect square on the left side: (x + 3)(x + 3) = 27 Calculate the square root of the right side: 5.196152423 Break this problem into two subproblems by setting (x + 3) equal to 5.196152423 and -5.196152423.Subproblem 1
x + 3 = 5.196152423 Simplifying x + 3 = 5.196152423 Reorder the terms: 3 + x = 5.196152423 Solving 3 + x = 5.196152423 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + x = 5.196152423 + -3 Combine like terms: 3 + -3 = 0 0 + x = 5.196152423 + -3 x = 5.196152423 + -3 Combine like terms: 5.196152423 + -3 = 2.196152423 x = 2.196152423 Simplifying x = 2.196152423Subproblem 2
x + 3 = -5.196152423 Simplifying x + 3 = -5.196152423 Reorder the terms: 3 + x = -5.196152423 Solving 3 + x = -5.196152423 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + x = -5.196152423 + -3 Combine like terms: 3 + -3 = 0 0 + x = -5.196152423 + -3 x = -5.196152423 + -3 Combine like terms: -5.196152423 + -3 = -8.196152423 x = -8.196152423 Simplifying x = -8.196152423Solution
The solution to the problem is based on the solutions from the subproblems. x = {2.196152423, -8.196152423}
| 9y+3-2y+7= | | 6(X+5)-(4x-4)= | | 2(3p-1)-3(p-4)= | | 78200/(68*46)= | | 6p+10q=400 | | logx^2-1=0 | | (5x^5y^7)^-2/10x^3y^5 | | 56ab/a=0 | | .07(18000-x)+.1x=1590 | | M^4+4m^2-12=0 | | 2a+6b=100 | | 3x-18/9-x= | | 9=3x^2-3x | | sin(2x)+3cos(2x)=0 | | f(-1)=3/(x^5) | | 3x+104=0 | | 5x-4p=27 | | 4x+22=-17+7x | | X-3-5=3 | | 2c+14=6-5 | | 1/5w-3=6/5w | | (9x-y)=0 | | 4x+28=340 | | p+(-2)=6 | | (-3)-3= | | 3x+y=2480 | | v/3=2 | | 5w+5=w-10 | | -116=4x+2(-6x-10) | | 4x-2=-5x+18-2x | | -11x-82=-148 | | 4x-5(-x-2)=9 |